1996
DOI: 10.1021/ja954081o
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nα-Acyl Chain Length on the Membrane-Modifying Properties of Synthetic Analogs of the Lipopeptaibol Trichogin GA IV

Abstract: Trichogin GA IV, an 11-residue lipopeptaibol blocked at the N-terminus by an n-octanoyl group and at the C-terminus by a 1,2-amino alcohol (l-leucinol), extracted from the fungus Trichoderma longibrachiatum, exhibits remarkable membrane-modifying properties. We have synthesized trichogin GA IV and several [l-Leu-OMe11] analogs carrying at the N-terminus an acyl chain of variable length (C2−C8, C10, C12, C14, C16, C18). A succinoylated head-to-head dimer was also prepared. A conformational analysis, carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 89 publications
(134 citation statements)
references
References 17 publications
(24 reference statements)
8
126
0
Order By: Relevance
“…with trichogin GA IV itself may well be associated with the higher number of carbon atoms present in the lipophilic chain of the former peptide. In fact, we have already shown [3] that the membrane activity of trichogin GA IV increases with increasing number of carbon atoms in the N h -blocking fatty acyl moiety.…”
Section: Conformational Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…with trichogin GA IV itself may well be associated with the higher number of carbon atoms present in the lipophilic chain of the former peptide. In fact, we have already shown [3] that the membrane activity of trichogin GA IV increases with increasing number of carbon atoms in the N h -blocking fatty acyl moiety.…”
Section: Conformational Analysismentioning
confidence: 88%
“…In these lipopeptides, a N h -blocking fatty acyl moiety of at least six carbon atoms is required for the onset of significant membrane activity [3]. In an NMR investigation in an aqueous solution containing SDS micelles we have shown that the acyl chain interacts intramolecularly with the first four amino acid residues [4].…”
Section: Introductionmentioning
confidence: 97%
“…The synthesis and characterization of Z-Gly-Leu-Aib-Gly 2 -Leu-Aib-Gly-Ile-Leu-OMe (Z: benzyloxycarbonyl) and its short sequences have already been reported. 26 As TOAC is unstable under the acidic and reducing conditions required to remove the classical tert-butyloxycarbonyl and Z groups, respectively, the Fmoc N ␣ -protecting group was chosen SCHEME 1…”
Section: Peptide Synthesismentioning
confidence: 99%
“…The spectrum of [Leu-OMe 11 ] trichogin GA IV 26 is also reported for comparison. In this alcohol all of the spectra exhibit a negative maximum at 206 -204 nm ( 3 * peptide transition) and a less intense negative shoulder at 229 -222 nm (n 3 * peptide transition).…”
Section: ϫ4mentioning
confidence: 99%
See 1 more Smart Citation